Caracterização da reserva faunística costeira de Tibau do Sul – REFAUTS, Rio Grande do Norte: proposta de ordenamento do turismo - Nascimento, Larycynthia Luana Sousa do (Universidade Federal Rural do Semi-Árido, 2016)
The Coast Wildlife Reserve of Tibau do Sul - REFAUTS is located at Pipa bay, southern coast of Rio Grande do Norte, and has as main objectives the conservation of coastal and marine biodiversity, especially marine turtles and Guiana dolphin, Sotalia guianensis, often found in the Madeiro and Dolphins bay. Given the growth in ecotourism at REFAUTS in the past decade, this study had as main objectives: (i) describe the economic-tourist activity in this Reserve; (ii) characterize the dolphin watching and the tourist profile that participated of the tours; (iii) evaluate the intensity of the tourist flow in this Reserve and (iv) estimate the tourism carrying capacity of the REFAUTS. To this end, there were five expeditions to the study area- three expeditions in 2014 and two expeditions in 2015, totaling 19 sampling days. Data collection in the study area occurred between 9:00h and 16:00h. In this study, we recorded 29 tourism enterprises at Madeiro bay and 5 tourism enterprises at Dolphins bay. We recorded 11 licensed vessels conducting tours for Guiana dolphin watching at REFAUTS. The tours occurred from 9:00h to 16:00h, with greater tourist flow between 11:00h and 11:30h. Tourists that participated in boat tours at REFAUTS were mostly young women, ofBrazilian national, with higher education and originating of the southeastern Brazil. From the evaluation of tourist flow, the number of tourists, surfers and kayaks was higher in Madeiro bay than in the Dolphins bay. However, the number of vessels did not differ between the two bays. The number of tourists registered in the study area was higher than the estimated tourism carrying capacity. Although REFAUTS was created in 2006, it still does not have a management plan for tourism planning. This study refers to the first proposal for tourism planning at REFAUTS, based on the current tourist flow, on the tourist profile and on the carrying capacity of the Reserve
Keywords: Boto-cinza; Plano de manejo; Praia de Pipa; Sotalia guianensis; Turismo de observação de golfinhos; Guiana dolphin; Management plan; Pipa Beach; Sotalia guianensis; dolphinwatching; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE